The relationship between non-monetary benefits and department of livestock production and development employees (civil servants) commitment - Mandizvidza, Onasis Vincent (Midlands State University, 2015)
The study sought to identify, if there is relationship between non-monetary benefits and the Department of Livestock Production and Development employees commitment. The researcher tried to find out how the following factors tangible, social and job-related non-monetary benefits contribute to employees commitment and retention. Applicable literature and theories were reviewed. The researcher employed the quantitative research paradigm. A survey research design administering Likert-scale questionnaires was used to collect data. The data was presented in pie charts, bar charts, tables and analyzed using descriptive statistics. The results showed that social non-monetary benefits have high relationship with employee commitment compared to tangible and job related non-monetary benefits. On the other hand demographic factors such as designation, age, work experience and educational qualification also play a role in motivating employees to be committed. Recommendations were made and these include: The need to review rewards monthly, leadership style, good and clear communication, role of line managers and directions for future researchers on this research topic of the relationship between non-monetary benefits and employee commitment